Relevansi adopsi manajemen Jepang dalam kerangka pengembangan sumber daya manusia dan industrialisasi di Indonesia: Pendekatan proses dan keterkaitan ekonomi - Akhmad Muhadi (Economic Journal of Emerging Markets, 1997)
TheJapanese transplants in Indonesia have been playing an important role on the process of industrialization in Indonesia. As the "World class" plants, theysupport to the establishment of the Indonesian's industrial performance. They characterized by their best production system based on the technology and the high quality and productivity based on the human resource development system. It is proved that those systems created such value chain by producing product in high competitive advantages in the world market. By adopting the Japanese Management. Indonesia which has low-cost labor, will create strategic advantages perform in technology with low-cost production'. As for Indonesian Government, the competitive advantages are the important aspects for anticipating the Free Trade Market system in 2003 according to AFTA agreement, and also APECagreement in 2020. Nowadays. Indonesian Government's Second Long-run Development Program has been holding the key concept: Human Resource Development Here, the discussion about the human resource development strategy on the Japanese transplants in Indonesia will come up. especially in the process of adoption of the Japanese Management.